Four species of Noctuoidea (Lepidoptera), new to Korea - Choi, Sei-Woong; Heo, Un-Hong; Kim, Sung-Soo (Zootaxa, 2021)
One species of Noctuidae, Chytonix brunneofascia Choi and Heo sp. nov., and three species of Erebidae, Gynaephora atrata Choi, Heo and Kim sp. nov., Utetheisa pulchelloides Hampson, and Pilipectus prunifera (Hampson) were newly recorded from Korea. This paper provides the diagnosis, descriptions of the adult and larva, and genitalia of the available species.